Pentingnya Guru PAK Dalam Mengatasi Kenakalan Peserta Didik Kristen di SMP Negeri 2 Sompak Kecamatan Sompak Kabupaten Landak - Agustinus Koamesak; Ina Martha; Ridolfroa S.Th Manggoa (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
There has been delinquency among some students at SMP Negeri 2 Sompak. Examples of student delinquency that often occur are skipping school during class hours, smoking during class hours or outside class hours, and not having responsibility for doing school work or homework given by the teacher. Therefore, Christian religious education teachers are needed to educate, teach and guide students so that acts of delinquency do not occur again. The aim of the research is to explain the importance of PAK teachers in overcoming the delinquency of Christian students at SMP Negeri 2 Sompak so that students become role models for their family, church and the Indonesian nation they love. The author uses qualitative research methods using observation, interviews, documentation and literature techniques. The results found were that if PAK teachers were more committed and responsible in dealing with the delinquency of Christian students, then Christian students would increasingly experience changes in their lives from acts of delinquency. Conclusion: Religious Education teachers who serve at SMP Negeri 2 Sompak must be committed and responsible in overcoming the delinquency of Christian students at SMP Negeri 2 Sompak so that students are able to show commendable attitudes in family, church, national and state life now and forever.